2020
DOI: 10.1002/aenm.202001972
|View full text |Cite
|
Sign up to set email alerts
|

Designing Advanced Lithium‐Based Batteries for Low‐Temperature Conditions

Abstract: requirements over the time of use, including variable rates, and pressures, and often most critical, temperatures. [2-4] The required low-temperature capabilities, shown in Figure 1, can present a critical roadblock toward the use of lithium-ion batteries. Commercial state-of-the-art batteries see noticeable drops in capacity retention and rate capability below 0 °C, and will rarely be recommended for use below −20 °C. [5] This limitation is defined by the kinetics of ion-transfer in solution; at low-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
193
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(202 citation statements)
references
References 92 publications
(131 reference statements)
0
193
0
Order By: Relevance
“…The reverse is similar for discharge, suggesting that the desolvation process is also required while Li + goes back into the cathode [20] . Therefore, it is reasonable that traditional LIBs encounter kinetics hindrance at low temperatures and high rates [4, 5, 36] . By contrast, Na + –ether co‐intercalation in SDIB would occur in the AG anode to generate ternary GICs during the charge process, [33–35] while the PTPAn could capture anions from the electrolyte by the triphenylamine radical cation [19, 25] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse is similar for discharge, suggesting that the desolvation process is also required while Li + goes back into the cathode [20] . Therefore, it is reasonable that traditional LIBs encounter kinetics hindrance at low temperatures and high rates [4, 5, 36] . By contrast, Na + –ether co‐intercalation in SDIB would occur in the AG anode to generate ternary GICs during the charge process, [33–35] while the PTPAn could capture anions from the electrolyte by the triphenylamine radical cation [19, 25] .…”
Section: Resultsmentioning
confidence: 99%
“…Rechargeable lithium‐ion batteries (LIBs) have witnessed widespread applications in portable electronics, electric vehicles and grid energy storage systems owing to their high energy, long life and low self‐discharge [1–3] . However, the increasing demand is gradually pushing LIBs to their limits, especially in fast charge and low temperature applications [4, 5] . For conventional LIBs, solvated lithium ions experience the desolvation step at the solid electrolyte interphase of electrolyte/electrode prior to the intercalation into bulk electrodes [6–10] .…”
Section: Introductionmentioning
confidence: 99%
“…Lithium‐ion batteries (LIBs) represent promising energy storage devices in portable electronics and electric vehicles, because of their advantages of high energy density, long cycle life, and low self‐discharge rate. [ 1‐7 ] However, there is serious performance degradation at lower temperatures which greatly prohibits their applications in cold climates. [ 8‐14 ] At low temperatures, the viscosity of electrolyte increases accompanied by a decrease in ionic conductivity, which results in a rapid increase of electrode polarization.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…These applications feature highly diverse and varying working environments with overcharge/discharge, high pressure, external forces, and often most critical, high/low temperature. [ 1–4 ] For example, LIBs lose most of their capacity, power, and cycle life when operated below ambient temperature. It has been reported that, at −40 °C, conventional LIBs only retained ≈12% of their room‐temperature capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [ 1–3 ] have utilized several enlightened approaches to analyze the decreased capacity of LIBs and have identified various factors that could deteriorate the LIB performance at low temperatures. The sluggish lithium‐ion diffusion in the electrolyte is generally regarded as the main reason for the unsatisfactory LIB performance under low‐temperature conditions.…”
Section: Introductionmentioning
confidence: 99%